2019
DOI: 10.1016/j.jclinepi.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A review of NICE appraisals of pharmaceuticals 2000–2016 found variation in establishing comparative clinical effectiveness

Abstract: To date, a small number of appraisals by NICE based on non-RCT data did not result in substantially different treatment decisions. The majority of the technologies appraised on the basis of non-RCT data either received a positive recommendation or a positive recommendation with restrictions. The methods used to calculate comparative clinical effectiveness estimates varied, highlighting the need to establish clear guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…In the absence of comparative data at the time of drug and device approval, many health technology assessment organisations and payers resort to using data with varying levels of limitations and uncertainty. 58 Current evidence standards may give patients and clinicians false reason for optimism that new treatments are beneficial and safe. 59,60 Clinicians and patients often overestimate the quality and quantity of evidence supporting new treatments.…”
Section: A Fragmented Evidence Base For Decision Making In Health Sysmentioning
confidence: 99%
“…In the absence of comparative data at the time of drug and device approval, many health technology assessment organisations and payers resort to using data with varying levels of limitations and uncertainty. 58 Current evidence standards may give patients and clinicians false reason for optimism that new treatments are beneficial and safe. 59,60 Clinicians and patients often overestimate the quality and quantity of evidence supporting new treatments.…”
Section: A Fragmented Evidence Base For Decision Making In Health Sysmentioning
confidence: 99%
“…via non-randomised studies) that requires appropriate methodologies that are not always taken into account. A review of NICE appraisals of pharmaceuticals (2000-16) by Anderson et al [148] found variations in establishing comparative clinical effectiveness. Of 489 individual pharmaceutical technologies assessed by NICE, 22 (4%) used non-RCT data to estimate comparative clinical effectiveness, with the methods for establishing external controls including: 13 (59%) used published trials, 6 (27%) used observational data, 2 (9%) used expert opinion and 1 (5%) used a responder vs non-responder analysis.…”
Section: Informing Decisions In Healthcare: a Discussion Related To Vmentioning
confidence: 99%
“…Furthermore, in an unblinded trial, knowledge of treatment received can lead to bias in the reporting of outcomes. Methodological guidance is needed to deal with non-RCT evidence [26]. Guidelines on the circumstances in which the submission of non-RCT evidence is acceptable would also be helpful.…”
Section: Key Methodological Issuesmentioning
confidence: 99%